Ta có: \(2n^2-n-1=2n^2+3n-4n-6+5=n\left(2n+3\right)-2\left(2n+3\right)+5\)
Vì \(n\left(2n+3\right)\)và \(-2\left(2n+3\right)\)chia hết cho \(2n+3\) nên để \(2n^2-n-1\)chia hết cho \(2n+3\) thì \(5\)phải chia hết cho \(2n+3\), tức là \(2n+3\inƯ\left(5\right)=\left\{1;-1;5;-5\right\}\)
Với \(2n+3=1\)thì \(n=-1\)
Với \(2n+3=-1\) thì \(n=-2\)
Với \(2n+3=5\)thì \(n=1\)
Với \(2n+3=-5\) thì \(n=-4\)
Vậy, để đa thức \(2n^2-n-1\) chia hết cho đa thức \(2n+3\) thì \(n=\left\{-2;-1;1;-4\right\}\) và \(n\in Z\)